Nurturing Both Organizational and Human Resource Wellbeing for Sustainable Growth - Rean, Markus Anto; Ibrahim, Muhdi B. Hi; Irawan, Andri; Akbar, Muhammad Aldrin; Rasyid, Abdul (Advances: Jurnal Ekonomi & Bisnis, 2024)
This study aims to explore the relationship between organizational sustainability and human resource wellbeing, emphasizing the strategic imperatives for fostering sustainable growth and success in contemporary organizations. Adopting a comprehensive literature review approach, the study examines the theoretical foundations, managerial implications, and practical strategies associated with nurturing both organizational and human resource wellbeing. The methodology involves synthesizing findings from diverse perspectives, including organizational sustainability, human resource management, and leadership studies. Results indicate that organizational sustainability serves as a cornerstone for long-term viability, encompassing financial stability, operational efficiency, stakeholder relationships, and environmental responsibility. Additionally, human resource wellbeing emerges as a critical determinant of organizational performance, innovation, and employee engagement, influenced by factors such as leadership style, organizational culture, and employee wellbeing initiatives. The study highlights the importance of integrating sustainability principles into organizational strategies, fostering supportive leadership, and investing in comprehensive employee wellbeing initiatives to create environments